Chinese policy toward Russia and the Central Asian Republics - Burles, Mark, 1970- (RAND, 1999)
This report examines the foundation of China's policies toward Russia and the five republics of Central Asia, identifies the combination of issues and environmental conditions likely to shape the policies' evolution, and assesses their potential impact on regional or global U.S. interests. After discussing why China has improved its relations with Russia, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, the report describes the goals of Chinese policies toward these countries, highlighting the wide range of issues and interests involved. The report next examines the prospects for Sino-Russian and Sino-Central Asian relations, and how the development of these relations might affect U.S. interests. China's relationships with the Central Asia Republics pose fewer potential problems for U.S. interests than does its relationship with Russia. There is little threat of China dominating the region in a manner that would restrict U.S. access to energy resources. Other aspects of China's relationship with the Central Asian states might become problematic; for example, land-based transportation links through Central Asia to the Middle East may facilitate greater economic, political, and military cooperation between Beijing and regional regimes that are hostile to the United States.